The Fourth Amendment : select issues and cases - Huff, Lucille E. (Laws and legislation series., 2014)
Before there were emails, instant messaging, and other forms of electronic communication, it was much easier for the courts to determine if a government investigation constituted a Fourth Amendment ""search."" If the police intruded on your person, house, papers, or effects-tangible property interests listed in the text of the Fourth Amendment-that act was considered a search, which had to be ""reasonable"" under the circumstances. However, with the advent of intangible forms of communication, like the telephone or the Internet, it became much more difficult for judges to determine when certai